Consistency of Post-Employment Remuneration Contract with Efficient Contract - Haidar Faqih Fadhilah; Mona Selvia Sibuea; Lia Uzliawati (International Forum of Researchers and Lecturers, 2025)
This study examines the implementation of post-employment remuneration within corporations, focusing on compliance with PSAK 24 standards and its alignment with efficient contract theory. The research emphasizes the importance of financial reporting in ensuring transparent, accurate, and accountable management of employee compensation obligations. Using PT Tigaraksa Satria Tbk as a case study, the study evaluates the consistency of post-employment contracts and their impact on corporate financial stability. Key findings reveal that precise actuarial calculations and adherence to regulations are critical for maintaining a balance between organizational obligations and financial sustainability. The paper also highlights risks related to changes in actuarial assumptions and investment performance, offering strategic recommendations to optimize post-employment benefits management. This research provides valuable insights into improving corporate governance and fostering stakeholder confidence through robust financial accountability.